Pelaksanaan Salat Jumat di Rumah Mengikuti Siaran Radio Menurut Pemikiran Syekh Ahmad Bin Siddiq Al-Ghummari - Asysyairazi Abdul Wahid (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
The Friday prayer is fardu 'ain for every male Muslim, this has become an ijma' (agreement) without any difference of opinion among the scholars. According to most scholars, Friday prayers are carried out in congregation with an uninterrupted row of empty more than 9 people, whereas if one row of rows of shaf is empty there are less than nine people, that is fine. However, the conditions for the validity of Friday prayers such as those that must be performed in the city, with a certain number, must be carried out in a mosque and there is no mention of the implementation of Friday prayers, according to Sheikh Ahmad bin Siddiq Al-Ghummari, these conditions do not have the proof of sharia. to her. It is strengthened again by the interpretation of the meaning of ذكرالله in verse 9 of surah al-Jumuah. This word literally means